Quantitative sonic transit time analysis defines multiple Permian– Cretaceous exhumation events during the breakup of Gondwana - Olierook, Hugo; Timms, Nick (2015)
The Perth Basin in southwestern Australia has an extended history involving multiple regional unconformity-forming events from the Permian to Cretaceous. The central and southern Perth Basin is the closest basin to the relict triple junction of eastern Gondwana and comprises a complete Permian to Recent stratigraphy, thus recording the full history of the breakup events. We use sonic transit time analysis to quantify the magnitudes of net exhumation and the minimum differences in net exhumation across different time intervals (here called ‘interval exhumation’) for four stratigraphic periods from 37 wells. We were able to quantify the minimum interval exhumation of the Permian–Triassic, Triassic–Jurassic, Early Cretaceous breakup and post-Early Cretaceous events. The Permian– Triassic and Triassic–Jurassic events recorded spatially varied exhumation, up to 1000 m, across sub-basins. These localized variations are caused primarily by reverse (re-) activation of NW-and N-striking faults in the Permian–Triassic and Triassic–Jurassic events, respectively. The Valanginian breakup unconformity (~133 Ma) records approximately 400 m of basin-wide interval exhumation during the breakup of Gondwana, which implies a change to relatively uniform exhumation on a regional scale. Using published uplift rates for volcanic and non-volcanic passive margins, estimates of the time required for 400 m of exhumation vary from 6 to 20 Ma, respectively. A volcanic margin is far more likely given that post-breakup sedimentation commenced 2–7 Ma after breakup. Lastly, post-breakup interval exhumation ranges from 0 to 800 m. The highest values are in the hangingwall blocks of faults. Up to 200 m may be locally caused by reverse fault re-activation due to the present-day compressional stress state of Australia. The remainder is attributed to regional exhumation caused by dynamic topography in the last 50 Ma.